Penyuluhan Inovasi Produk Perikanan melalui Peran Sentral Perempuan untuk Mendukung Kemandirian Ekonomi Pesantren Putri di Bandar Lampung - Noor, Huriyatul Fitriyah; Jati, Ciptaning Weargo; Septi Malidda Eka Putri; Henky Mayaguezz (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Pesantren (Islamic boarding schools) play a vital role not only asreligious educational institutions but also as agents of community-basedeconomic development. This outreach program on fishery product innovation,conducted in a female pesantren in Bandar Lampung, aimed to enhance theeconomic capacity of the institution through the empowerment of women. Theprogram covered materials on local fishery potential, innovative processingtechniques, business management, and environmental sustainability. It wasdelivered through presentations, group discussions, hands-on practice, androle-playing methods. The results showed significant improvement inparticipants’ knowledge and skills in processing and managing fisheryproducts, along with heightened awareness of the central role of women inpesantren-based economic development. This initiative proved effective infostering entrepreneurship among women in the pesantren environment andserves as a strategic effort to promote institutional economic self-reliance. Thismodel is expected to be replicable in other pesantren as part of inclusive andsustainable local economic development